Transcatheter Aortic Valve Implantation (TAVI) In Small Island Nation- Maldives, Leading Cardiac Care to A Higher Standard - Tiwari, Kaushal Kishore; Shafiu, Mohamed; Barakoti, Murari; Nema, Ashish Kumar; Kumar, Athul Suresh; Razzag, Dusooma Abdul; Manandhar, Diwas; Sai, Satish (Journal of National Heart and Lung Society Nepal, 2024)
Background: Surgical aortic valve replacement is still considered the preferred treatment option for patients with severe aortic valve stenosis, and it is known to improve the survival of the patients. However, about 30-50% of patients are not operated on due to several reasons including old age, high risk and other comorbidities. Transcatheter Aortic Valve Implantation (TAVI) is emerging as an alternative treatment option for elderly patients with high surgical risk. Methods: In our study, four patients have undergone TAVI from February 2022 till May 2023 using Medtronic Transcatheter Aortic Valve, Core valve Evolut R (Medtronic Inc., Minneapolis, MN, USA) bioprosthesis. Results: All the patients were discharged early. Follow-up Echocardiography showed decreased transaortic gradient with improved quality of life. Conclusion: We conclude, implementation and use of this emerging technology in small Island Nations like Maldives would help to treat many patients, mostly elderly and high-risk as well as patients with intermediate risk requiring aortic valve surgery with less morbidity and comparable mortality in comparison to SAVR.